Agricultural marketing : systems, coordination, cash, and futures prices - Purcell, Wayne D. (Reston, Va. : Reston Pub. Co., 1979)
Comes in six parts namely: Marketing in perspective; The market system and the operating environment; Prices and price analysis; Commodity futures and hedging; Decision models, techniques, market strategies; Current issues and a look ahead.
Includes bibliographical references and index.
oif 01/02/2019
Loans
Keywords: Farm produce; Agriculture--Economic aspects; Marketing; United states